2020
DOI: 10.21037/gs.2020.01.16
|View full text |Cite
|
Sign up to set email alerts
|

One-step prepectoral breast reconstruction with porcine dermal matrix-covered implant: a protective technique improving the outcome in post-mastectomy radiation therapy setting

Abstract: Background: Post-mastectomy radiotherapy (PMRT) applied on implant-assisted immediate breast reconstruction (IBR) involves a marked increase in complication rate. The recent opportunity of performing an ADM-assisted prepectoral breast reconstruction (PPBR) raised the hypotesis of a protective interaction between ADM and periprosthetic tissues under PMRT.Methods: We performed a retrospective monocentric analysis of a cohort of consecutively treated patients undergone one-step PPBR between January 2015 and Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…They found no significant risk of implant loss 1.1% vs 3.6%, rippling of 0.6% vs 0, seroma 8% vs 7.1%, and infection 5.2% vs 0 between the two groups. However, the capsular contracture rate was higher in the PMRT group, 10.7% compared to non-PMRT group 0.6%, which was statistically significant 37,38 . In comparison, the effect of PMRT in patients who had subpectoral implant-based breast reconstruction versus prepectoral one, contracture rate was significantly higher for the subpectoral patients with PMRT than for the prepectoral patients with PMRT (52.2 vs 16.1%; P=0.0018) 24 .…”
Section: Breast Reconstruction and Radiotherapymentioning
confidence: 78%
See 3 more Smart Citations
“…They found no significant risk of implant loss 1.1% vs 3.6%, rippling of 0.6% vs 0, seroma 8% vs 7.1%, and infection 5.2% vs 0 between the two groups. However, the capsular contracture rate was higher in the PMRT group, 10.7% compared to non-PMRT group 0.6%, which was statistically significant 37,38 . In comparison, the effect of PMRT in patients who had subpectoral implant-based breast reconstruction versus prepectoral one, contracture rate was significantly higher for the subpectoral patients with PMRT than for the prepectoral patients with PMRT (52.2 vs 16.1%; P=0.0018) 24 .…”
Section: Breast Reconstruction and Radiotherapymentioning
confidence: 78%
“…In patients with Prepectoral breast reconstruction with ADM's or synthetic mesh with postmastectomy radiotherapy, we found studies to be in favour of use of radiotherapy 31,37,38 . Prepectoral breast reconstruction group had minimal or comparable complication rates (25% in irradiated vs 23% in the non-irradiated group) compared with the subpectoral group (Table 2).…”
Section: Leonardo Cattelani Susanna Polottomentioning
confidence: 88%
See 2 more Smart Citations
“…According to the literature, the stimulation and differentiation of ASCs increase wound repair and regeneration ability by intensifying collagen secretion and deposition [9,14]. Recent studies have demonstrated a link between adipocytes and wound healing, given that adipocytes also act as key regulators of skin health [28]. Collected data showed that in vitro colonisation capacity and adipogenic differentiation potential of ASCs are membrane dependent.…”
Section: Discussionmentioning
confidence: 99%